Implementasi Kebijakan Dalam Penyediaan Ruang Terbuka Hijau Publik Melalui Peraturan Daerah Nomor 7 Tahun 2010 tentang Penataan Ruang Terbuka Hijau di Kota Semarang - Taufiq Ardiansyah; Suwanto Adhi; Wiwik Widayati (Journal of Politic and Government Studies, 2014)
AbstractGreen areas in Semarang city have been change into housing and building. This problem happened because increasingly the growth of infrastructure. Many buildings around of centre of Semarang city cause decreasing of green areas. Based on that case, the local goverment formed regulation number 7th in 2010 about management of green areas in Semarang city.This research aimed to find out implementation of that regulation in Semarang and how people can be involved in this policy. Research method using qualitative with descriptive data.Theory of Edward III explained that four variables to observe the implementation of policy : communication, resources, disposition, and bureaucracy structure. In communication through socialization of some green activities conducted by local departement of planning development (Bappeda) with green communities, developer, and people. Resource variables divided into two aspects; human and financial resource. Human resources include department of planning development, department of city and housing estate, institute of environmental, and department of garden and sanitation. Meanwhile, financial resource comes from the budget. Disposition variable has been implemented well. Some services and training has been held by department of planning development to developer and green communities. They also provide meeting to increase the responsibility for the policy. In bureaucracy structure, goverment expand the link with some companies to increase green areas. Unfortunately, there are no many companies which involved in this activity yet. Goverment should give more concern about that.2The implementation of regulation also persuade people to actively support green areas in Semarang. Developer, green comunities, and people supposed to be responsible and participate in this policy well. This regulation has been implemented well enough by all of people. It also one of some efforts to solve decrease problem of green areas in Semarang. It will be supposed to give positive value to other people.Key words : Implementation, regulation, green area